Hyperthecosis: an underestimated nontumorous cause of hyperandrogenism. (3rd August 2021) - Meczekalski, Blazej; Szeliga, Anna; Maciejewska-Jeske, Marzena; Podfigurna, Agnieszka; Cornetti, Paulina; Bala, Gregory; Adashi, Eli Y.
Abstract: Hyperthecosis is defined as the presence of nests of luteinized theca cells in the ovarian stroma. Persistent testosterone released by ovarian theca cells is unmasked postmenopausally through the loss of granulosa cell-mediated aromatization of testosterone to estradiol. Ovarian hyperthecosis (OH) usually presents with symptoms of hyperandrogenism and is often described as a severe or extreme form of Polycystic Ovary Syndrome (PCOS). Serum testosterone levels in excess of 150 ng/dl (>5.2 nmol/l) are seen in affected patients and this threshold is used to confirm a diagnosis. Treatment of hyperthecosis is multi-faceted. It addresses the attendant hyperandrogenism (hirsutism and virilization) as well as metabolic complications such as obesity and insulin resistance. Ultimately, laparoscopic bilateral salpingo-oophorectomy is definitive treatment. This remains the treatment of choice in postmenopausal women whereas treatment using GnRH agonists may be used in women of reproductive age, especially younger women. Nevertheless, if serum testosterone remains elevated despite several months of therapy with a GnRH agonist, surgery is often required for biopsy sample collection and further definitive therapy. In order to mitigate the common clinical manifestations of hyperandrogenism, anti-androgen therapy (either cyproterone acetate or spironolactone) may be used to suppress the actions of testosterone on tissues. In patients with impaired glucose metabolism and insulin resistance, Metformin should also be considered as part of treatment. Combined, such a treatment regimen will often lead to decreased ovarian androgen secretion.